Beyond Recursion: Critique of Hauser, Chomsky, and Fitch - Taraban, Roman; Achintha Bandara (East European Journal of Psycholinguistics, 2017)
In 2002, Hauser, Chomsky, and Fitch published an article in which they introduced a distinction between properties of language that are exclusively part of human communication (i.e., the FLN) and those properties that might be shared with other species (i.e., the FLB). The sole property proposed for the FLN was recursion. Hauser et al. provided evidence for their position based on issues of evolution. The question of the required properties of human language is central to developing theories of language processing and acquisition. In the present critique of Hauser et al. we consider two examples from non-English languages that argue against the suggestion that recursion is the sole property within the human language faculty. These are i) agreement of inflectional morphemes across sentence constructions, and ii) synthetic one-word constructions.ReferencesAdger, D. (2003). Core Syntax: A Minimalist Approach. Oxford: Oxford University Press.Bates, E., & MacWhinney, B. (1989). Functionalism and the Competition Model. In: The Crosslinguistic Study of Sentence Processing, (pp 3-76). B. MacWhinney and E. Bates (Eds.). New York: Cambridge University Press.Bickerton, D (2009). Recursion: core of complexity or artifact of analysis? In: Syntactic Complexity: Diachrony, Acquisition, Neuro-Cognition, Evolution, (pp. 531–543). T. Givón and M. Shibatani (Eds.). Amsterdam: John Benjamins.Chomsky, N. (1957). Syntactic Structures (2nd edition published in 2002). Berlin: MoutonChomsky, N. (1959). On certain formal properties of grammars. Information and Control, 2, 137–167.Chomsky, N. (1995). The Minimalist Program for Linguistic Theory. Cambridge, MA: MIT Press.Hauser, M. D., Chomsky, N., Fitch, W. T. (2002). The faculty of language: What it is, who has it, and how did it evolve? Science, 298, 1569-1579.Luuk, E., & Luuk, H. (2011). The redundancy of recursion and infinity for natural language. Cognitive Processing 12, 1–11.Marantz, A. (1997). No escape from syntax: Don't try morphological analysis in the privacy of your own lexicon. University of Pennsylvania Working Papers in Linguistics, 4(2), A. Dimitriadis, L. Siegel, et. al. (eds.), 201- 225.MacWhinney, B. & O’Grady, W. (Eds.) (2015). Handbook of Language Emergence. New York: Wiley.Nevins, A., Pesetsky, D., & Rodrigues, C. (2009). Pirahã exceptionality: A reassessment. Language, 85(2), 355–404.Ott, D. (2009). The evolution of I-language: Lexicalization as the key evolutionary novelty. Biolinguistics, 3, 255–269.Sauerland, U., & Trotzke, A. (2011). Biolinguistic perspectives on recursion: Introduction to the special issue. Biolinguistics, 5, 1–9.Trotzke, A., Bader, M. & Frazier, L. (2013). Third factors and the performance interface in language design. Biolinguistics, 7, 1–34.